1998
DOI: 10.1109/55.728902
|View full text |Cite
|
Sign up to set email alerts
|

Narrow width effects of bottom-gate polysilicon thin film transistors

Abstract: The effects of channel width on the characteristics of both hydrogenated and unhydrogenated bottom-gate polysilicon thin-film transistors (TFT's) were investigated in detailed. For unhydrogenated and silane gas formed TFT's, a drastic decrease in threshold voltage is observed due to the grain-boundary traps are reduced when the channel width is reduced to less than grain size, but the minimum drain current sensitive to intragranular tail states are nearly unchanged. After hydrogenation, almost grain boundary t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…At high V ds the high-field tunnelling mechanism becomes dominant, causing device leakage to depend on the number of traps within the TFT [6]. As the channel dimension is equal to or smaller than grain size, a large-dimensional TFT has more traps [7], thus showing the tunnelling phenomenon at lower V ds (∼−10 V). We have proposed a model to explain this post-stressed swing variation of unhydrogenated TFTs as follows: the schematic energy diagram of the TFTs under off-state stress is shown at the bottom of figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…At high V ds the high-field tunnelling mechanism becomes dominant, causing device leakage to depend on the number of traps within the TFT [6]. As the channel dimension is equal to or smaller than grain size, a large-dimensional TFT has more traps [7], thus showing the tunnelling phenomenon at lower V ds (∼−10 V). We have proposed a model to explain this post-stressed swing variation of unhydrogenated TFTs as follows: the schematic energy diagram of the TFTs under off-state stress is shown at the bottom of figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…In many other electronic devices, short channel [26] and narrow width effects [27][28][29] become important in this range. To test the validity of the assumption, a-Si:H transistors with Ti Schottky barrier source/drain contacts and Effective Channel Width W eff (μm) a common back gate have been fabricated and characterized.…”
Section: Discussionmentioning
confidence: 99%
“…However, all of the TFTs studied were in small-grain polysilicon with significantly larger trap densities. Only Yaung et al [19] reported a V th increase with decreasing channel width for hydrogenated polysilicon TFTs, where the trap density is reduced.…”
Section: Channel Geometry Effectsmentioning
confidence: 99%